Molecular Genetic Analysis of Midgut Serine Proteases in Aedes aegypti Mosquitoes - Isoe, Jun (2009)
Digestion of blood meal proteins by midgut proteases provides anautogenous mosquitoes with the nutrients required to complete the gonotrophic cycle. Inhibition of protein digestion in the midgut of blood feeding mosquitoes could therefore provide a strategy for population control. Based on recent reports indicating that the mechanism and regulation of protein digestion in blood fed female Aedes aegypti mosquitoes is more complex than previously thought, we used a robust RNAi knockdown method to investigate the role of four highly expressed midgut serine proteases in blood meal metabolism. We show by Western blotting that the early phase trypsin protein (AaET) is maximally expressed at 3 h post blood meal (PBM), and that AaET is not required for the protein expression of three late phase serine proteases, AaLT (late trypsin), AaSPVI (5G1), and AaSPVII. Using the trypsin substrate analog BApNA to analyze in vitro enzyme activity in midgut extracts from single mosquitoes, we found that knockdown of AaSPVI expression caused a 77.6% decrease in late phase trypsin-like activity, whereas, knockdown of AaLT and AaSPVII expression had no significant effect on BApNA activity. In contrast, injection of AaLT, AaSPVI, and AaSPVII dsRNA inhibited degradation of endogenous serum albumin protein using an in vivo protease assay, as well as, significantly decreased egg production in both the first and second gonotrophic cycles (p<0.001). These results demonstrate that AaLT, AaSPVI, and AaSPVII all contribute to blood protein digestion and oocyte maturation, even though AaSPVI is the only abundant midgut late phase serine protease that appears to function as a classic trypsin enzyme.